(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
This study investigates the optimization of crude pectinase concentration for clarifying bael juice, which contains fibrous pulp that limits juice recovery. The effects of different pectinase concentrations, incubation times, and temperatures on juice yield and turbidity were analyzed. The results showed that a 3% crude pectinase concentration, incubated for 60 minutes at 45°C, produced the highest juice yield (67.8%) and the lowest turbidity (568 NTU). The study underscores that the optimal conditions for maximizing juice yield while minimizing turbidity involve a careful balance of enzyme concentration and incubation parameters.